SOWING HARMONY: INCLUSIVE EDUCATION FOR ACTIVE TOLERANCE IN MULTICULTURAL SCHOOLS OF THE LAND OF RAFFLESIA - Moch. Iqbal; Betti Dian Wahyuni; Wachid Ridwan (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to explore the practice of active tolerance in the multicultural school in Bengkulu City. The school is known, for its diversity, being a multicultural institution with students of diverse ethnicities and religions. This research employed a qualitative research with a case study design involving school principals, Islamic teachers, students, and parents of students at SMA Sint Carolus, Bengkulu City. Data were collected through participatory observation to understand school interactions, in-depth interviews, and document analysis to understand the school's curriculum and religious materials. Using qualitative research methods with a field research approach provides more space to explore the implementation of active tolerance more deeply in Catholic schools. This study showed that the implementation of three strategic efforts, the Dual Lens Curriculum, the Empathy Circle Forum, and the Communal Solution Project, significantly transformed students' character from passive tolerance to inclusive active tolerance. The findings revealed that strengthening cognitive flexibility through multi-perspective materials and developing radical empathy in a safe encounter space successfully broke down prejudice and primordial barriers in multicultural schools. The implications of this research emphasized the importance of synergy between schools and families. This research proved that respect for self-identity rooted in the home was the main key in building organic solidarity and sustainable harmony in Bumi Rafflesia.